2002
DOI: 10.1017/s0031182002001658
|View full text |Cite
|
Sign up to set email alerts
|

The trouble with sealworms (Pseudoterranova decipiens species complex, Nematoda): a review

Abstract: Sealworms or codworms, larvae of ascaridoid nematodes belonging to the Pseudoterranova decipiens species complex, infect the flesh of numerous species of marine and euryhaline fish, and have proven a chronic and costly cosmetic problem for seafood processors. Moreover, the parasite may cause abdominal discomfort in humans when consumed in raw, undercooked or lightly marinated fish. In this review, the phylogeny, life cycle and distributions of sealworms are discussed along with biotic and abiotic factors which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(132 citation statements)
references
References 0 publications
2
125
1
4
Order By: Relevance
“…Regarding parasite prevalence there was a tendency of regional variation, in that Atlantic cod appeared to become more quickly infected in the Sisimiut area than in the Godthaab area. Similar geographical variation has been observed off Canada, and may in part reflect the distribution of the phocid and cetacean definitive hosts (McClelland et al 1983, Brattey and Bishop 1992, Boily and Marcogliese 1995, McClelland 2002. However, it is difficult to quantify this difference and it is at present impossible to evaluate if the distribution of definitive hosts, which determines nematode composition in this area, influences parasite accumulation in the species studied here.…”
Section: Nematode Prevalence and Intensitysupporting
confidence: 63%
See 1 more Smart Citation
“…Regarding parasite prevalence there was a tendency of regional variation, in that Atlantic cod appeared to become more quickly infected in the Sisimiut area than in the Godthaab area. Similar geographical variation has been observed off Canada, and may in part reflect the distribution of the phocid and cetacean definitive hosts (McClelland et al 1983, Brattey and Bishop 1992, Boily and Marcogliese 1995, McClelland 2002. However, it is difficult to quantify this difference and it is at present impossible to evaluate if the distribution of definitive hosts, which determines nematode composition in this area, influences parasite accumulation in the species studied here.…”
Section: Nematode Prevalence and Intensitysupporting
confidence: 63%
“…Furthermore, their presence in muscle tissue of cod is of economic importance due to the hygienic problems they cause in the fishing industry (McClelland 2002). Also, parasites are usually able to regulate their host population (Begon et al 1996, Mouritsen and Poulin 2002, Møller 2005) and where these parasitic nematodes occur abundantly they might well affect the cod population negatively.…”
Section: Introductionmentioning
confidence: 99%
“…Buchmann and Kania (2012) indicated that prevalence and intensity of P. decipiens in Baltic cod has increased over the last 30 yr. The zoonotic potential of P. decipiens is potentially higher than C. osculatum because larvae of the former species almost exclusively are found in the fish musculature (Mcclelland 2002;Skirnisson 2006). We detected only one cod worm in the investigated .…”
Section: Discussionmentioning
confidence: 99%
“…Las larvas de anisákidos en los peces comercializados también tiene un impacto económico sobre la industria por la pérdida que ocasiona su detección y extracción de los músculos del bacalao (Gadus morhua) y otros peces demersales como ha sido demostrado en la costa atlántica de Canadá, calculándose una pérdida de 27 a 50 M de dólares anualmente (McClelland 2002).…”
Section: Parásitosunclassified